The CaMV 35S enhancer contains at least two domains which can confer different developmental and tissue-specific expression patterns - Benfey, Philip N. (1989)
We have analyzed expression conferred by two domains from the cauliflower mosaic virus (CaMV) 35S promoter and found different patterns in seeds, seedlings and seven week old plants. Expression from domain A (-90 to +8) is strongest in the radicle of the embryo, the radicle pole of the endosperm and in root tissue of seedlings and mature plants. Expression from domain B (-343 to -90) is strongest in the cells adjacent the cotyledon of the endosperm, in the cotyledons of the embryo and seedings and in the leaves and stem of mature plants. When both domain A and domain B are present expression is detectable in most tissues at all stages of development. Thus analysis of a constitutive promoter in transgenic plants can be used to identify cis elements that confer tissue specific and developmentally regulated expression.